Bridging Intentional and Formal Models: An Agent-Oriented RE Framework Integrating i and CASL - Salama Eisa Ali Abudalrasul (Surman Journal of Science and Technology, 2024)
The growing complexity of software systems necessitates rigorous analysis during the early stages of requirements engineering (RE). While Goal-Oriented RE (GORE) frameworks like i∗i∗ are excellent for capturing stakeholder intentions and social dependencies, they lack formal semantics for precise verification. Conversely, formal methods often operate at a level of detail removed from high-level organizational reasoning. This paper presents a novel agent-oriented RE methodology that bridges this gap by integrating the informal, intentional modeling of the i∗i∗ framework with the formal, mental-state-based specifications of the Cognitive Agents Specification Language (CASL). We introduce Intentional Annotated Strategic Rationale (iASR) diagrams, an extension of i∗i∗’s SR models, augmented with composition and link annotations to provide the precision needed for formal mapping. We define a systematic mapping from iASR diagrams into CASL, enabling the formal analysis of agent goals, knowledge, and interactions. The framework’s utility is demonstrated through a detailed meeting scheduler case study, showing how it supports the verification of requirements consistency, goal decompositions, and epistemic feasibility. The key contribution is a seamless, traceable path from high-level, intentional models to verifiable, executable agent specifications.